Inducible defence against a ciliate grazer Pseudomicrothorax dubius, in two strains of Phormidium (cyanobacteria) - Fialkowska, E. (1997)
Experiments were done with two strain of filamentous, mat-forming Phormidium and their ciliate grazer Pseudomicrothorax dubius, to explain why the ciliates remain hungry in an apparent surplus of food, except for the first 24 hours after feeding. Under grazing pressure, both strains of cyanobacteria showed statistically significant increases in the number of filaments terminating in an empty sheath, compared to the control. Direct observations revealed that the mechanism behind this effect was active withdrawal of the trichomes inside the sheaths when disturbed by grazers. As P. dubius is unable to ingest trichomes with such endings, we conclude that cyanobacteria are not limited to chemical means of defence against grazers but can also defend themselves by means of movement and changes in filament morphology. This is apparently the first report on behavioural defence observed in cyanobacteria.